2022
DOI: 10.1108/ejm-06-2021-0386
|View full text |Cite
|
Sign up to set email alerts
|

Stressful eating indulgence by generation Z: a cognitive conceptual framework of new age consumers’ obesity

Abstract: Purpose This study aims to delineate the phenomenon of stressful eating within generation Z due to the times they are living in and to extract propositions which elucidate phases of stressful eating within Zers. Design/methodology/approach Based on relevant literature on consumer obesity, theories of pure impulse buying and reasoned action, cognitive constructs eminent for reasoned conditioned behaviour are extracted. Followed by extraction of the reasoned conditioned behaviour and its cognitive constructs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Similar results were reported by Čukelj et al [33], who showed a clear relation between habits and emotions. While it is not compelling that younger generations are more emotionally mature and resilient, our findings are in accordance with a study [37] that looked at stressful eating habits of Generation Z. Another study [38], which focused exclusively on the female Generation Z population, found mixed attitudes toward eating habits, with some females having eating disorders.…”
Section: Nutritional Awareness and Interest In Health And Nutritional...supporting
confidence: 90%
“…Similar results were reported by Čukelj et al [33], who showed a clear relation between habits and emotions. While it is not compelling that younger generations are more emotionally mature and resilient, our findings are in accordance with a study [37] that looked at stressful eating habits of Generation Z. Another study [38], which focused exclusively on the female Generation Z population, found mixed attitudes toward eating habits, with some females having eating disorders.…”
Section: Nutritional Awareness and Interest In Health And Nutritional...supporting
confidence: 90%
“…In Park and Lee’s study (2020), the authors found that high perceived stress was one of the significant influencing factors for higher consumption of convenience foods. Similarly, Priporas et al (2022) reported that Gen Zers initially strive to make health-conscious choices but eventually fall into the cycle of constricting self-controlling behaviors and stressful eating indulgence, leading to obesity. Considering these consumer behaviors, future convenience store designers should aim to provide healthier choices while also meeting emotional desires and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has emphasized how gen z's love for social media and related isolation, as well as poor diet, are affecting their short-and long-term health (Priporas et al, 2022). In addition, previous studies about gen z's interaction with technology have also demonstrated their tech savviness and willingness to adopt new technologies (Romero & Lado, 2021) as well as how their interaction with mobile content leads to their engagement (Mulier et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggest that individuals often ruminate when encountering self‐threat (Ray et al, 2005) and some ruminate a great deal more than others (Nolen‐Hoeksema et al, 2008). Prior research identifies that rumination can increase self‐critical valuation, thereby influencing individuals to correct their behaviors and correspond with the social good (Bushman et al, 2005; Denson et al, 2011; Pedersen et al, 2011).…”
Section: Hypothesis Developmentmentioning
confidence: 99%